The INOWAS platform: A web-based numerical groundwater modelling approach for groundwater management applications. (September 2022) - Glass, Jana; Junghanns, Ralf; Schlick, Robert; Stefan, Catalin
Abstract: The INOWAS Decision Support System (DSS ) is an open-source web-service for groundwater management applications, in particular managed aquifer recharge. It is accessible via the interactive graphical user interface (GUI) running in a standard web browser and includes tools of varying complexity. The platform provides the user with features to set up, run and analyse numerical groundwater flow and transport models based on the USGS MODFLOW family and the possibility to set up, run and compare various groundwater management scenarios. The applicability of the web-based approach is demonstrated by the simulation of groundwater flow at a case study site in Pirna, Germany. Highlights: INOWAS DSS web-service for groundwater management applications has been developed. Numerical groundwater flow models can be set up, run and analysed in a web browser. Groundwater management scenarios can be created, simulated and compared.